Penulisan Naskah Drama Menggunakan Aplikasi Wattpad pada Mahasiswa - Yani, Dalu Ahmad; Nadya, Nyayu Lulu; Amalia, Falina Noor (Universitas Galuh, 2025)
This research aims to study, analyze, and understand the elements in drama script writing, focusing on the suitability of content, the completeness of intrinsic elements and structure, and the linguistic rules of drama scripts. This study uses a qualitative descriptive method to describe the condition of students' drama script writing. Data were collected through a drama script writing test with a romance theme, which was given to 16 6th semester Indonesian Language and Literature Education students at Tridinanti University. Data validity was tested using triangulation techniques, and data analysis was carried out through data reduction, data presentation, and conclusion drawing. The results showed that the Wattpad application was effective in helping students write drama scripts. Students are able to develop story ideas, diction, language styles, and creative imagination by utilizing Wattpad. Overall, students showed an increase in drama script writing skills after using the Wattpad application as a learning medium. Wattpad can be a relevant, interesting, and interactive learning media in learning literature, especially drama script writing. The utilization of Wattpad can help students adapt to technological advances and create more effective literature learning.Keywords: Writing; Drama script; Romance; Wattpad; Student